APPLICATION OF MODERN APPROACHES TO THE DEVELOPMENT OF ECONOMIC ACTIVITY IN INDUSTRIAL ENTERPRISES - Z.Xojimurodov (International Journal of Innovations in Engineering Research and Technology, 2021)
This article reveals the topic of increasing the economic activity of industrial enterprises through the application of modern approaches, the industrialization of production, the application of effective and modern methods of its management. The cited quotations and analyzes show that the authors have taken an in-depth approach to the study of the issue. The theoretical and scientific observations in the article written as a result of this research are presented as a rich resource for the researchers of the subject.